Diálogos socrático-platônicos e interdisciplinaridade no ensino de filosofia na EJA - Santos, Fabíola Maria Moreira dos (2024)
This research has as its theme the teaching of Philosophy at EJA and its general objective is to think of a methodology to facilitate the learning of Philosophy content at CEJA. The methodology applied aims to encourage reflection and discussion on the Socratic-Platonic dialogical horizon, adopting an analytical-exploratory study of bibliographic references and documentary sources. The theoretical reference of this research is in Plato's Philosophy, more specifically in the “Allegory of the Cave”, which narrates the ascension to the world of true ideas, beyond shadows and illusions. It is also based on Paulo Freire's pedagogy, for the contributions made to Youth and Adult Education. Bibliographical studies and observation of the dynamics of Philosophy teaching at the Raquel Castro e Silva de Miranda Youth and Adult Education Center allowed this research to be carried out. At the center, teaching in this modality takes place by area of knowledge and in the interdisciplinary model. We consider that Philosophy is capable of freeing us from the condition of ignorance in which men live, its teachings lead to the knowledge of the truth and its presence in the basic education curriculum, bringing light to the teaching and learning of other sciences. It is believed that the teaching of Philosophy can lead to knowledge of the essence of things, that it is the awakening to an education based on truth, capable of forming critical and participatory citizens in the construction of an ideal State. This research has as its product a Philosophy teaching plan for Youth and Adult Education.